What Lobbying Ethics and What for? The Case of French Lobbying Consulting Firms - Rival, Madina (Journal of business ethics, 2018)
Conversely to the United States, lobbying consulting in France is a relatively recent activity and is perceived negatively by a majority of the population. Influencing public decision-making is certainly a sensitive occupation at both managerial and societal levels. This is why ethics applied to business can play a central role while establishing the practice of lobbying in France. This paper examines the issues and the practices of ethics in lobbying consulting. The field for this exploratory study is a lobbying consultancy firm based in France. Our research is developed through a 3-month participant observation and complemented with secondary data on the lobbying profession in France. The results of this research are developed along two lines: (1) The practice of ethics in lobbying consultancy firms reveals its limits as well as a framework worth developing. The players and the represented client topics are potential dangers for ethical lobbying firms. This intervention research has nevertheless allowed us to observe the emergence of an effective regulation approach: the ethics of exemplarity as potentially illustrated by a representative actor of the French lobbying consulting profession. (2) The stakes of ethics are both internal and external to lobbying consulting professionals in France. Internally, ethics act as a structuring element enabling this profession to establish itself with practices and deontological codes; externally, it clarifies the relationship between lobbying consultants and their major stakeholders including customers, government, and the civil society.